Functional Tricuspid Regurgitation: Behind the Scenes of a Long-Time Neglected Disease - Vinciguerra, Mattia; Sitges, Marta; Luis Pomar, Jose; Romiti, Silvia; Domenech-Ximenos, Blanca; D'Abramo, Mizar; Wretschko, Eleonora; Miraldi, Fabio; Greco, Ernesto (Frontiers in Cardiovascular Medicine, 2022)
Severe tricuspid valve regurgitation has been for a long time a neglected valve disease, which has only recently attracted increasing interest due to the notable negative impact on the prognosis of patients with cardiovascular disease. It is estimated that around 90% of tricuspid regurgitation is diagnosed as ‘‘functional’’ and mostly secondary to a primary left-sided heart disease, and therefore has been usually interpreted as a benign condition that did not require a surgical management. Nevertheless, the persistence of severe tricuspid regurgitation after left-sided surgical correction of a valve disease, particularly mitral valve surgery, has been associated to adverse outcomes, worsening of the quality of life and a mortality rate significant increase. Similar results have been found when the impact of isolated severe tricuspid regurgitation has been studied. Current knowledge is shifting the ‘‘functional’’ categorization towards a more complex and detailed pathophysiological classification, identifying various phenotypes with completely different etiology, natural history and, potentially, an invasive management. The aim of our review is to offer a comprehensive guide for clinicians and surgeons with a systematic description of ‘‘functional’’ tricuspid regurgitation subtypes, an analysis centered on the effectiveness of existing surgical techniques and a focus on the emergent percutaneous procedures. This latter may be an attractive alternative to a standard surgical approach in patients with high-operative risk or isolated tricuspid regurgitation.